Relationship between oral cinacalcet therapy with CRP and anemia in hemodialysis patients with secondary hyperparathyroidism - Hoseininia, Saeed; Kebar, Sousan Mohammadi; Matin, Somaieh; Sadeghieh-Ahari, Saeed; Salemi, Helia (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Cinacalcet is one of the newest calcium mimetic drugs in the treatment of patients with parathyroid cancer, secondary hyperparathyroidism in adults with chronic kidney disease. Due to the possible association between the effect of Cinacalcet on C-reactive protein and the pathophysiology of anemia in end-stage renal disease patients. The aim of this study was to evaluate the effect of oral Cinacalcet on rate of CRP and anemia in ESRD patients with secondary hyperparathyroidism. Methods: This descriptive cross-sectional study was done on all 40 hemodialysis patients over 18 years of age underwent hemodialysis for at least 6 months. The levels of C-reactive protein, phosphorus, calcium, parathyroid hormone, ferritin, Total iron binding capacity, iron, hemoglobin before the start of treatment and based on the routine dialysis ward were repeated once every three months and recorded in the, in the checklist. Also, age, sex, weight, underlying disease, duration of dialysis and duration of use and dose of Cinacalcet were entered. The results of these experiments were reviewed and analyzed before and after treatment with Cinacalcet. Results: In these patients, after treatment with Cinacalcet, the amount of hemoglobin increased and the amount of inflammation decreased and these changes were significant in hemoglobin rate but not significant in CRP rate. The relationship between patients’ weight and inflammation was significant. Conclusions: Treatment with Cinacalcet in hemodialysis patients, at least in this study, could be increased hemoglobin and decreased CRP rate and can be a hypothesis for large analytical studies.